Perbandingan Kadar Endapan Nikel Laterit Pada Front Penambangan Dengan Stockpile Pada PT Ceria Nugraha Indotama: Comparison of Laterite Nickel Deposit Levels on the Mining Front with Stockpile at PT Ceria Nugraha Indotama - Ardhana, Muh. Reza; Thamsi, Alam Budiman; Anshariah, Anshariah (Journal of Engineering Science and Technology Applications, 2023)
PT Ceria Nugraha Indotama is a company engaged in mining laterite nickel ore in Wolo sub-district, Kolaka district, Southeast Sulawesi province. In lateritic nickel ore mining activities, there is often a difference in levels of laterite nickel ore when it is still in the mining front and after being transferred to the stockpile. This research is to determine the proportion of differences in the levels of Ni, Fe, MgO and SiO2 on the mining front with the stockpile and to determine the factors that influence changes in nickel content. The method used in this study is the grab sampling method in front mining and stockpile. The results of this study are based on the results of the analysis, obtained data on the levels of Ni, Fe, MgO and SiO2 on the mining front with a stockpile, the Ni content has a difference of 0.05% and the Fe content has a difference of 0.34%, the two minerals have the highest grades on the mining front. mining and MgO content has a difference of 2.68% and SiO2 content has a difference of 8.87%, the two minerals have the highest grade in the stockpile. Factors that influence changes in nickel content are the heterogeneous distribution of ore, the position of the waste above the ore and the rainy weather that occurs in the field, operator and sampling skills.